2013
DOI: 10.1007/s10103-013-1415-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pretreatment on Er:YAG laser-irradiated dentin

Abstract: Erbium:yttrium-aluminum-garnet (Er:YAG) laser preparation of tooth cavities for restoration is an increasingly popular method, but its compatibility with existing composite material bonding protocols has not been fully defined. This study evaluated the effect of laser and etchant pretreatments on the performance of one-bottle self-etch adhesives in Er:YAG laser-prepared dentin. Eight groups of 20 extracted teeth were established to investigate bonding in tested dentin disks. Various combinations of laser prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 21 publications
0
16
0
2
Order By: Relevance
“…9 Additionally, Chen et al reported that Er:YAG laser conditioning may not compromise self-etching adhesives efficacy when employed for dentin conditioning. 30 Based on the evaluation of all outcome parameters defined in this in vitro study, the etching protocols could be grouped into 4 categories according to SBS values and statistical analysis. Optimal adhesion includes phosphoric acid and phosphoric acid + Er:YAG laser groups, followed by appropriate adhesion for self-etching group, sufficient adhesion for Er:YAG laser and Er:YAG laser + phosphoric acid groups.…”
Section: Discussionmentioning
confidence: 99%
“…9 Additionally, Chen et al reported that Er:YAG laser conditioning may not compromise self-etching adhesives efficacy when employed for dentin conditioning. 30 Based on the evaluation of all outcome parameters defined in this in vitro study, the etching protocols could be grouped into 4 categories according to SBS values and statistical analysis. Optimal adhesion includes phosphoric acid and phosphoric acid + Er:YAG laser groups, followed by appropriate adhesion for self-etching group, sufficient adhesion for Er:YAG laser and Er:YAG laser + phosphoric acid groups.…”
Section: Discussionmentioning
confidence: 99%
“…SEM and TBS analysis from Chen et al demonstrated that both low-level laser energy pretreatment and acid etching reduced irregularities and produced a more homogeneous surface, signifi cantly increasing the tensile bond strength of adhesion to the irradiated dentin [ 43 ].…”
Section: Fig 730mentioning
confidence: 99%
“…A study by showed that the Er, Cr:YSGG radiation at a low pulse energy of 3.13 mJ, delivered at an incidence angle of 5° to the dentin slice surface, resulted in signifi cant bacterial reduction up to a dentin thickness of 500 μm [ 101 ].…”
Section: Laser Effects On Bacteriamentioning
confidence: 99%